2021
DOI: 10.2147/cmar.s337271
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Expression in Endometrial Serous Carcinoma and Its Prognostic Significance

Abstract: Purpose Programmed death-ligand 1 (PD-L1) has been widely used as a prognostic biomarker and an immunotherapeutic target in numerous cancers, but information on the clinical significance of its expression in endometrial serous carcinoma (ESC) is largely lacking. Here, we evaluate the predictive value of PD-L1 expression in ESC. Materials and Methods A total of 79 cases of ESC accessioned between January 2003 and September 2015 were selected for further analysis. PD-L1 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The combination of PARP inhibitors and immune checkpoint inhibitors considerably improves the prognosis of gynecologic cancer patients and promotes the long-term benefits following maintenance therapy in the era of personalized precision medicine where targeted and immunotherapy are common 14 . Furthermore, Zhang et al and Chen et al demonstrated the predictive importance of PD-L1 expression in endometrial serous cancer 15 , 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The combination of PARP inhibitors and immune checkpoint inhibitors considerably improves the prognosis of gynecologic cancer patients and promotes the long-term benefits following maintenance therapy in the era of personalized precision medicine where targeted and immunotherapy are common 14 . Furthermore, Zhang et al and Chen et al demonstrated the predictive importance of PD-L1 expression in endometrial serous cancer 15 , 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy currently represents an attractive strategy for patients with EC, mainly those with advanced or recurrent disease, with no effective treatment options available after standard chemotherapy [ 93 ]. Given the high expression of PD-1/PD-L1 in EC, it is reasonable to test inhibitors targeting the PD-1-PD-L1 axis to treat EC [ 94 ]. Indeed, many studies have tested the efficacy of PD-1 or PD-L1 antibodies in different molecular subtypes of ECs.…”
Section: Exploiting the Interplay Between Ddr And Immunity For Cancer...mentioning
confidence: 99%
“…PD-L1 expression on tumor and immune cells can be detected using IHC and different PD-L1 commercial clones. PD-1 and PD-L1 play progressively important roles in our understanding of tumor immunology and antitumor treatment [ 19 ]. Binding of PD-L1 to its receptor PD-1 leads to T-cell inactivation in a variety of carcinomas [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Binding of PD-L1 to its receptor PD-1 leads to T-cell inactivation in a variety of carcinomas [ 20 ]. Therefore, anti-PD-1/PD-L1 treatment deregulates the adverse impact of tumor-infiltrating T-cells, which in turn may reverse the tumor immune resistance [ 19 ]. Several clinical and experimental studies have investigated PD-L1 expression in EC and its prognostic values as well as its efficacy as an immunotherapy for EC [ 21 , 22 , 23 ]; however, these studies focused on endometrioid carcinomas and did not consider MLA as a separate or independent group.…”
Section: Introductionmentioning
confidence: 99%